The awareness of personal financial management among students in UiTM Seremban 3 campus / Khairunnisa Asyila Khairudin - Khairudin, Khairunnisa Asyila (Faculty of Business and Management, 2014)
The project paper entitled “The Awareness of Personal Financial Management among Students in UiTM Seremban 3 Campus” was conducted from February 2014 to June 2014. The purpose of this research is to examine the awareness of personal financial management among UiTM students in Seremban 3. This study focuses on 3 important independent variables which are personal experience, purchasing behavior and also knowledge and skills. This study was conducted in UiTM Seremban 3 Campus where the data and statics are being taken. The hypothesis was supported by the result. 100 questionnaires have been distributed among students that stay in the UiTM. The researcher has obtained the data and analyzed it in SPSS 20.0 which involved frequencies, reliability, descriptive statistics, Pearson correlation and multiple regression analysis. Based on the findings, it shows that the personal experience is has no relationship with the dependent variable due to the negative value of the beta and also T-test. Whereas, purchasing behavior is the most significant and has a strong relationship with the dependent variable which is personal financial management due to the highest T-test value.